Claves simbólicas que alimentan la expresión violenta de las diferencias sociales. Chile, siglos XVIII-XIX - María Eugenia Albornoz Vásquez (Nuevo mundo - Mundos Nuevos, 2006)
In this paper we describe the analysis of proposed justifications for ordinary aggression among people, this in the context of the social values of a Hispanic-Catholic hierarchical society. We mainly focus on certain symbolic keys of the social order which feeds the expression of the social differences in a violent way. Their projection on time creates fragile social contexts that are beyond the original colonial situation. We have studied the judicial files for insults and injuries submitted to the tribunals of Chile between the 18th and 19th century. We compared the meaning of the different symbolic keys to their description in available dictionaries of that time.